Retrospective 10-year observation of complications associated with maintaining of catheters in the peritoneal cavity in parients treated with the method of the peritoneal dialysis - Mozul, Sławomir; Grzebalska, Agnieszka; Książek, Andrzej (Polish Journal of Public Health, 2011)
Introduction. Peritoneal dialysis has been applied as the chronic kidney-replacing procedure since the 70s of the 20th century. One of the essential conditions necessary for the appropriate conducting of the therapy of peritoneal dialysis is a correct function of the catheter implanted to the peritoneal cavity. Surgeons usually deal with implantation of catheters in peritoneal dialyses, but also at some centers nephrologists or treatment radiologists perform these. Aim. The purpose of the study is presenting own, retrospective observation concerning implantation of catheters in peritoneal dialysis by surgeons and nephrologists. Material and methods. Patients with the chronic final kidney failure treated with the method of peritoneal dialysis were subjected to a retrospective analysis of The Department of Nephrology, Medical University of Lublin in the years of 1998-2007. In that period 194 patients were treated with the method of peritoneal dialysis therapy. Catheters were implanted by nephrologists and surgeons. Nephrologists applied Seldinger method for implantation of catheters, surgeons – the so called ‘blind method’. Results. In retrospective observation conducted at our centre, it is possible to notice a larger number of catheters implanted by nephrologists in the number of 171, in proportion to the number of catheters established surgically – in the number of 23. A relative majority of the number of complications is also visible in the surgeon’s method although both applied methods are very similar to each other. Conclusions. Implantation of the catheter in peritoneal dialyses through the experienced nephrologists is a safe procedure, providing with the valuable, long-term access to the kidney-substitution treatment.